A hazai utánpótlás kosárlabda piaci helyzetének elemzése nemzetközi kitekintéssel. - Bakó Patrícia (2019)
The main focus of this thesis is basketball, which – besides studying – determines my everyday activities, and fills my life since I was 10 years old. The paper is based on the PEST analysis method, which examines the current situa-tion of sports organizations. It includes the operation of different sports organizations, what income and outcome they have, from where they might get financial support and how a sports organization as a business venture should be pictured. Within that also how controlling is embedded in that, what type of marketing tools they can use, and, of course the most outstanding factor also comes to the foreground: the social environment. Local senior teams, professional abilities and equipment all have big influence on local clubs' success, which also influences a country's success in sports. Important factors will be the motivation of children (experience of success, role models, etc.), how less tal-ented youngsters could be motivated, what influential factors of a club's efficiency there are, how the government can help make the basis for that from a social viewpoint, and why bigger population is an important factor, which is actually essential. In order to get the whole picture about the Hungarian situation, answers in form of questionnaire will help, which was filled out by the children playing at Soproni Darazsak Academy and their parents. According to the results of the research it can be said that the youngsters see the situation in a mature and realistic way, while the parents have surpris-ingly distinct opinions. Besides that interviews conducted with coaches and executives of four different teams coming from abroad will allow the analysis to get on an international level and so it would serve as a basis for comparison for the domestic situation. I have found many similarities, and many small details that if adopted could increase the Hungarian niveau and success rate. There are many similarities between the generations growing up now mostly in mentality, which are, of course, influenced by culture as well. To sum it up, we can say that the problem has many aspects. There is a problem with children getting more and more stubborn and lazy, who are difficult to motivate, with coaches who were not qualified further, who have to force to building up a better realtionship with the players and their parents, in order for the laetter tol isten to them in connection with the child’s future in basketball and the system itself, which allows too many international players, making the development and improvement of young Hungarian players impossible when they are age out of youth teams. Of course, there is always a solution to be found, but to do that many compromises and developments are necessary.